Alkaline rocks from a Proterozoic volcanic island in the Cape Smith Thrust Belt, New Quebec - Gaonac'h, H.; Picard, C.; Ludden, J.; Francis, D. (Geoscience Canada, 1989)
Summary In the Cape Smith Belt, a highly alkaline sequence of volcanic rocks overlies the tholeiitic basalts of the Povungnituk Group. This sequence consists of basanites/nephe-linites and phonolites. All lavas display high Zr, Nb, Ti values, and the mafic lavas containprimary titaniferous clinopyroxene. Crystal fractionation models indicate that the evolution of the mafic lavas was dominated by clinopyroxene fractionation. The phonolites are most reasonably interpreted as products of extensive fractionation of feldspar from abasanitic parent. The Cape Smith alkaline suite is similar toPhanerozoic undersaturated lava suites and is interpreted as part of an alkaline volcanic island developed on the continental margin of an opening oceanic rift basin. The chemistry of the alkaline rocks from the Cape Smith Belt suggests similar processes for the generation alkaline melts in the Proterozoic and Phanerozoic mantle.